Idiopathic generalized apical root resorption: a report of three cases - AILBHE McMULLIN, PADHRAIG S. FLEMING & ANDREW T. D (IAPD and Blackwell, 2008)
Resorption is a condition associated with either physiologic or pathologic processes resulting in a loss of dentin, cementum, or bone